2016
DOI: 10.1038/ncomms11343
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin phosphotransferase is an unusual antibiotic resistance kinase

Abstract: Rifampin (RIF) phosphotransferase (RPH) confers antibiotic resistance by conversion of RIF and ATP, to inactive phospho-RIF, AMP and Pi. Here we present the crystal structure of RPH from Listeria monocytogenes (RPH-Lm), which reveals that the enzyme is comprised of three domains: two substrate-binding domains (ATP-grasp and RIF-binding domains); and a smaller phosphate-carrying His swivel domain. Using solution small-angle X-ray scattering and mutagenesis, we reveal a mechanism where the swivel domain transits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…Overrepresentation of 3 KEGG pathways involved in metabolism was observed in the 5-FU group with hypergeometric distribution, which involved in the categories "Galactose metabolism" and "Phosphotransferase system (PTS)" (Supplementary Table S6). Enriched genes encoding PTS, which reflected increased representation of multiple carbohydrate transporters, was an important mechanism to confer resistance to selection pressure, such as antibiotic, as reported in the previous studies [21]. In the Oxi group, two KEGG pathways "Ribosome" and "Lysine biosynthesis" were significantly enriched.…”
Section: Functional Alterations In Gut Microbiota During the Chemothesupporting
confidence: 70%
“…Overrepresentation of 3 KEGG pathways involved in metabolism was observed in the 5-FU group with hypergeometric distribution, which involved in the categories "Galactose metabolism" and "Phosphotransferase system (PTS)" (Supplementary Table S6). Enriched genes encoding PTS, which reflected increased representation of multiple carbohydrate transporters, was an important mechanism to confer resistance to selection pressure, such as antibiotic, as reported in the previous studies [21]. In the Oxi group, two KEGG pathways "Ribosome" and "Lysine biosynthesis" were significantly enriched.…”
Section: Functional Alterations In Gut Microbiota During the Chemothesupporting
confidence: 70%
“…Resistance to rifamycin antibiotics in the clinic is predominantly due to point mutations in the target, the b subunit of RNA polymerase (Ramaswamy and Musser, 1998), although a rifampin ADP-ribosyltransferase (Baysarowich et al, 2008) (Arr-2) is found in many Gram-negative resistance plasmids. In contrast to the clinic, environmental bacteria have developed a rich diversity of mechanisms to inactivate the rifamycins including ADP-ribosyltransferases (Baysarowich et al, 2008), glycosyltransferases (Spanogiannopoulos et al, 2012), phosphotransferases (Qi et al, 2016;Spanogiannopoulos et al, 2012;Stogios et al, 2016), and monooxygenases (Andersen et al, 1997;Hoshino et al, 2010;Liu et al, 2016). The latter have been detected in a variety of bacteria (Nocardia farcinica, Rhodococcus equi) and are associated with decomposition of the antibiotic.…”
Section: Introductionmentioning
confidence: 99%
“…Rifampin phosphotransferases (Rph) transfer a phosphate to the C21 position of rifamycins and are widespread in environmental and some pathogenic bacteria, including Listeria monocytogenes [11,33]. This enzyme family is structurally related to phosphoenolpyruvate (PEP) synthases but has a unique domain architecture [33]. Combinations of different rifampin resistance elements in a single strain are known, but not paralogs of Rphs [10,11,34].…”
Section: B Brevis Vm4 Has Two Rifampin Phosphotransferase Pseudoparamentioning
confidence: 99%
“…We verified that both predicted rphs (rphC and rphD) confer rifampin resistance when heterologously expressed in E. coli (Table 1). Steady-state kinetic analysis of RphC and RphD revealed that both are catalysts for rifampin phosphorylation, and have a catalytic constant similar to other Rphs [9,11,33] (Supplementary Table 5). Rifampin directly interacts with RpoB by forming four essential hydrogen bonds.…”
Section: B Brevis Vm4 Has Two Rifampin Phosphotransferase Pseudoparamentioning
confidence: 99%